Refleksi Teori Kritis Jurgen Habermas atas Konsesus Simbolik Perda Syariah - Ahmad Abrori (Universitas Islam Negeri Jakarta, 2016)
This article aims to investigate how the critical theory of Jurgen Habermas can be used to better understand the Syariah Islamic law issues in the district of Garut. Habermas is arguably one of the most powerful thinkers in contemporary sociology, particularly because of his influential ideas regarding public sphere. He believes that the absolute power of the state by which it colonizes civic daily life should not automatically silence public voices. Modern capitalism creates huge opportunity of people to connect in public spheres such as markets, cafes, and restaurants. They do economic transaction at the same time they love to talk, discuss, and argue on current social, economics, and political issues. It leads to the society that might change the power of authority as well as the established culture, starting by questioning the public policy that might lead to the authority which has a legitimacy crisis. From this perspective, the implementation of Perda Syariah (Sharia local regulation) in Garut region is analyzed. This paper uncovers the conditions in which the law enforcement of the Perda has been challenged.DOI: 10.15408/ajis.v16i1.2897